Cognitive functions in euthymic bipolar I and II patients: a cross sectional study - Ilhan, Rifat Serav; Tatli, Safiye Zeynep; Demirel, Hilal; Cankorur, Vesile Şentürk (Frontiers in Psychiatry, 2025)
IntroductionThis study aimed to compare the neurocognitive profiles of euthymic patients with bipolar I (BD-I) and bipolar II (BD-II) disorder and healthy controls, while controlling for confounding clinical and pharmacological variables, to determine whether observed cognitive differences reflect true subtype distinctions or are secondary to illness burden.MethodsWe assessed 78 clinically stable outpatients with BD-I or BD-II and 40 healthy controls using a comprehensive neuropsychological battery that included tests of verbal episodic memory, executive functioning, processing speed, attention, and working memory. All patients were in euthymia and receiving stable monotherapy. Analyses of covariance (ANCOVA) were conducted to compare group performance, adjusting for age, illness duration, number of depressive episodes, hospitalizations, and chlorpromazine-equivalent doses of antipsychotics and mood stabilizers.ResultsBoth BD subtypes demonstrated significant cognitive impairments relative to controls. BD-I patients showed broader and more severe deficits, especially in verbal episodic memory and executive flexibility. Importantly, only verbal memory impairments remained significant after full covariate adjustment, indicating a potential trait-like vulnerability in BD-I. Differences in executive function, processing speed, and attention between BD-I and BD-II were primarily explained by illness severity and medication exposure. Verbal episodic memory represents a robust and subtype-specific cognitive impairment in BD-I, whereas other cognitive differences between BD-I and BD-II are primarily attributable to modifiable clinical factors.DiscussionThese findings underscore the importance of integrating cognitive evaluation into routine care and suggest that cognitive profiles may inform personalized interventions and diagnostic clarification in bipolar disorder.